What do Cochrane systematic reviews say about cardiac arrest management? - Rafael Leite Pacheco; Juliana Trevizo; Caio Augusto de Souza; Gabriel Alves; Bruno Sakaya; Luciana Thiago; Aécio Flávio Teixeira de Góis; Rachel Riera (São Paulo Medical Journal)
ABSTRACT CONTEXT AND OBJECTIVE: Cardiac arrest is associated with high morbidity and mortality and imposes a significant burden on the healthcare system. Management of cardiac arrest patients is complex and involves approaches with multiple interventions. Here, we aimed to summarize the available evidence regarding the interventions used in cardiac arrest cases. DESIGN AND SETTING: Review of systematic reviews (SRs), conducted in the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo. METHODS: A systematic search was conducted to identify all Cochrane SRs that fulfilled the inclusion criteria. Titles and abstracts were screened by two authors. RESULTS: We included nine Cochrane SRs assessing compression techniques or devices (three SRs), defibrillation (two SRs) and other interventions (two SRs on hypothermia interventions, one on airway management and one on pharmacological intervention). The reviews included found qualities of evidence ranging from unknown to high, regarding the benefits of these interventions. CONCLUSION: This review included nine Cochrane systematic reviews that provided a diverse range of qualities of evidence (unknown to high) regarding interventions that are used in management of cardiac arrest. High-quality evidence was found by two systematic reviews as follows: (a) increased survival until hospital discharge with continuous compression, compared with interrupted chest compression, both administered by an untrained person and (b) no difference regarding the return of spontaneous circulation, comparing aminophylline and placebo, for bradyasystolic patients under cardiac arrest. Further studies are needed in order to reach solid conclusions.